Management Practices and Feed Supplements on the Growth of Two Chicken Breeds (Gallus Domesticus L.) under Smallholders’ Farm Conditions: Case of Rajshahi - Islam, M. Saiful; Mustari, Sharmin (ABC Journal of Advanced Research, 2017)
The present study assessed the management practices and feed supplements on growth performance of two common chicken breeds viz., Fayoumi (an exotic) and Sonali (a crossbred) in 10 Upozillas or Police Stations of Rajshahi District. For the collection of experimental data every week, a government, 10 private and 10 backyard smallholders’ poultry farms were selected, and the investigation was conducted from January to December 2015. Fourteen such major management practices as feeding, vaccination, bio-safety measures, disposal of wastes and dead bodies were considered to rank the farms from excellent (score 5) to unacceptable (score 1) scales. All the parameters showed significant variation (P